2010
DOI: 10.1088/0268-1242/25/2/024005
|View full text |Cite
|
Sign up to set email alerts
|

Metal-catalyzed semiconductor nanowires: a review on the control of growth directions

Abstract: Semiconductor nanowires have become an important building block for nanotechnology. The growth of semiconductor nanowires using a metal catalyst via the vapor-liquid-solid (VLS) or vapor-solid-solid (VSS) mechanism has yielded growth directions in 1 1 1 , 1 0 0 and 1 1 0 etc. In this paper, we summarize and discuss a broad range of factors that affect the growth direction of VLS or VSS grown epitaxial semiconductor nanowires, providing an indexed glimpse of the control of nanowire growth directions and thus th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
242
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(249 citation statements)
references
References 147 publications
5
242
2
Order By: Relevance
“…22 As a result, the islands are preferentially propagated in the ⟨111⟩ direction because of the lowest surface energy in that direction for zinc-blende structured NWs (stage II). 23 As the NW grows, however, the interface gradually becomes inelastic and finally loses its 1-D nature. As a result, the height of In x Ga 1−x As NWs is saturated at a certain point (stage III).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…22 As a result, the islands are preferentially propagated in the ⟨111⟩ direction because of the lowest surface energy in that direction for zinc-blende structured NWs (stage II). 23 As the NW grows, however, the interface gradually becomes inelastic and finally loses its 1-D nature. As a result, the height of In x Ga 1−x As NWs is saturated at a certain point (stage III).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…They, moreover, constitute an important platform in the search for Majorana bound states [6,7]. Catalytical growth using a "bottom-up" self-assembly technique from nanoparticles provides numerous possibilities to manipulate crystal structure, morphology, and potential landscape [8]. Thereby, the nanowires, also often termed as nanorods or nanowiskers, are likewise highly interesting objects in the field of spintronics which exploits the spin degree of freedom of the electron in addition to its charge [9].…”
Section: Introductionmentioning
confidence: 99%
“…Nanowires made from diamond and zinc-blende type semiconductors tend to grow in the 111 crystal direction as it minimizes the free energy [8]. However, the direction can be effectively controlled by substrate orientation, surface chemical treatment, temperature, or pressure [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, controlling the nanowire growth direction may provide a new approach to obtain III-V semiconductor nanowires with controlled crystal phase and high structural quality. On the other hand, from a fundamental scientific point of view, the optical, electrical and mechanical properties of nanowires are expected to differ for nanowires with different growth directions [34,35], and previous studies have shown that the growth directions of nanowires can affect the nanowire properties [36][37][38]. In this regard, in order to better understand the relationship between the nanowires growth directions and their properties and, in turn, to better fulfil nanowire applications, it is critically important to accurately determine the growth directions of grown epitaxial nanowires.…”
Section: Introductionmentioning
confidence: 99%